A review of research advances in the modulation of olfactory receptors for COPD inflammation and airway remodeling - Zhu, Zhihao; Gong, Daohui; Chen, Yue; Yuan, Ming; Qian, Hang; He, Binfeng; Wang, Guansong (Frontiers in Immunology, 2025)
Chronic obstructive pulmonary disease (COPD), as the third leading cause of global mortality, presents complex pathological mechanisms and imposes a substantial health burden. Emerging evidence reveals that olfactory receptors (ORs), traditionally associated with odor detection, exhibit non-canonical regulatory functions in COPD pathogenesis. This review systematically explores ORs’ multidimensional roles: environmental triggers activate specific ORs in specific cells, initiating chronic inflammatory cascades. Persistent inflammation drives irreversible airway remodeling through smooth muscle proliferation and extracellular matrix reorganization. Preclinical and clinical studies demonstrate that OR agonists/antagonists modulate the inflammation-remodeling axis to influence pulmonary function, though their pleiotropic effects complicate therapeutic targeting. The cell type-specific expression patterns and diverse ligand profiles of ORs create unique opportunities for precision interventions, while posing challenges in tissue delivery and receptor efficacy optimization. Future investigations should integrate single-cell omics and artificial intelligence to elucidate OR-mediated dynamic networks, downstream signaling pathways, and their interplay with microbiome-gut-lung axis regulation. This review not only advances our understanding of OR biology in respiratory diseases but also proposes a novel theoretical framework for developing OR-based diagnostic and therapeutic strategies in the early management of COPD.